Potential Mineralisation of Gold and Base-Metals in the Bald Hill Region, South Westland, New Zealand - A F. Cooper (The Australasian Institute of Mining and Metallurgy, 2007)
The northeast-southwest trending ~25 km2 area incorporating Bald Hill is located 18 km northeast of Haast, and 5 - 7 km west of the Alpine Fault in South Westland, New Zealand. The geology consists of Greenland Group greywacke overlain by a Cretaceous-Tertiary sedimentary sequence and fluvio-glacial/marine terrace deposits of Quaternary age. Alluvial gold in Cole Creek, draining west from the summit of Bald Hill, may be derived either from vein mineralisation in basement rocks or from fluvial or marine terraces.   This paper focuses on the potential for in situ gold and base-metal mineralisation in sporadic, siderite-rich quartz veins that cut basement greenschist facies metasediments that have been overprinted by contact metamorphism.   Throughout the area, vein compositions are dominated by quartz and commonly feature zoned plagioclase. Alteration adjacent to veining within the contact aureole is dominated by 1 - 2 mm, coarse grained biotite, with small amounts of sulphide, and is pervaded by abundant siderite veinlets. Outside the aureole, wall rock alteration to veins consists of fine grained chlorite. Trace element XRF analysis has been used to ascertain base metal concentrations within samples of vein and alteration zones collected from throughout the area. Vein and alteration zone mineral assemblages containing <5 per cent sulphide, with low concentrations of As, Cu, Pb and Zn indicate low potential for gold and base-metal mineralisation in the Bald Hill region. Contact metamorphism of Greenland Group basement in the northeast of the region, is likely due to emplacement of a poorly exposed Cr- and Ni- enriched gabbro. The presence of biotite and andalusite in hornfelses indicate contact metamorphism occurred at temperatures >350¦C and at depths <10 km. Widespread vein distribution does not appear to be related to contact metamorphism or gabbro emplacement. Further research is required in order to establish the fluid source from which the veins were precipitated.